The story of Cirrus Flux - Skelton, Matthew 1971- (Delacorte Press, 2009)
In 1783 London, the destiny of an orphaned boy and girl becomes intertwined as the boy, Cirrus Flux, is pursued by a sinister woman mesmerized, a tiny man with an all-seeing eye, and a skull-collecting scoundrel, all of whom believe that he possesses an orb containing a divine power
Originally published: London : Penguin Books, 2009
The gallows tree -- The girl behind the curtain -- Blackguards! -- The house in Midas Row -- Mr. Leechcraft -- Twelve years earlier -- The House of Mesmerism -- Black Mary's hole -- Across London -- The dark room -- The silver timepiece -- Twelve years earlier -- The boy who did not exist -- The face at the window -- Cirrus, alone -- The scioptric eye -- The hall of wonders -- The moon-sail -- Eleven years earlier -- The halcyon bird -- The hanging boy -- The fallen angel -- The celestial chamber -- Escape! -- The breath of God -- H-O-P-E.
Keywords: Geschichte 1700-1800; Geschichte; Great Britain / History / George III, 1760-1820 / Fiction; London (England) / History / 18th century / Fiction; Großbritannien; Kinderbuch